Method for preparing g-C3N4 / biochar with high photocatalytic activity through molten salt pyrolysis of sewage and sludge and application of g-C3N4 / biochar

By using sewage sludge as a carbon source, biochar and g-C3N4 are combined by molten salt pyrolysis method, solving the complex and cost-effective synthesis of existing materials, and realizing the preparation of high-photocatalytic active materials and the effective utilization of waste.

CN119951550AActive Publication Date: 2025-05-09CHANGJIANG RIVER SCI RES INST CHANGJIANG WATER RESOURCES COMMISSION

Patent Information

Application Number
CN202510128634.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-05-09
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

The synthesis steps of existing g-C3N4/biochar composites are complex, have long preparation cycles, high cost, and the catalytic performance needs to be further improved, which cannot meet the performance requirements.

Method used

By using sewage sludge as a carbon source, biochar and g-C3N4 are combined by molten salt pyrolysis method to increase the specific surface area of ​​the material, promote electron transfer, and thus improve photocatalytic activity.

Benefits of technology

The high photocatalytic activity g-C3N4/biochar material was prepared, with a narrow band gap width and a large visible light absorption range, excellent photocatalytic activity, and the rational utilization of waste was achieved through the utilization of sewage and sludge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119951550A_ABST
    Figure CN119951550A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing g-C3N4 / biochar with high photocatalytic activity through molten salt pyrolysis of sewage and sludge and application of the g-C3N4 / biochar, and belongs to the technical field of energy catalysis and environmental restoration. The method for preparing g-C3N4 / biochar from sewage sludge through molten salt pyrolysis comprises the following steps: drying the sewage sludge to obtain sludge powder; mixing the sludge powder with melamine to obtain a mixed material precursor, then mixing the mixed material precursor with a molten salt medium, and performing pyrolysis treatment to obtain the g-C3N4 / biochar. According to the invention, sewage sludge is used as a carbon source to compound biochar and g-C3N4, so that the specific surface area of the material can be increased, electron transfer is promoted, and the photocatalytic activity is improved. The prepared photocatalytic material is narrow in band gap width, large in visible light absorption range and excellent in photocatalytic activity, meanwhile, sewage sludge serves as a carbon source, and reasonable utilization of waste is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy catalysis and environmental restoration, and in particular to a method for preparing g-C3N4 / biochar with high photocatalytic activity by pyrolyzing sewage sludge with molten salt and an application thereof. Background Art

[0002] Energy crisis and environmental pollution are two major problems that need to be solved in today's society. Both urgently require relevant researchers to make continuous efforts to develop new solutions. Among them, photocatalytic technology, with its broad application prospects, no secondary pollution and environmentally friendly characteristics, provides solid scientific support for the sustainable use of energy and the restoration of the ecological environment. In this technology, the development and preparation of new and efficient photocatalytic materials is the main research focus.

[0003] Compared with titanium dioxide, zinc oxide and other photocatalytic materials, graphite carbon nitride (g-C3N4), as a polymer semiconductor material, has high thermal and chemical stability, good electron conduction ability, excellent photoelectric properties and suitable redox potential, and has great research value. However, the lamellar structure of pure g-C3N4 leads to a small specific surface area, and there are many defects such as easy recombination of photogenerated electrons and holes, fewer reactive active sites, and easy agglomeration. By adopting modification strategies such as building heterojunctions, morphology control, and heteroatom doping, the above defects of g-C3N4 can be improved to a certain extent, and its photocatalytic activity can be improved, but there is still room for further improvement.

[0004] One of the research and development directions is to compound carbonaceous materials with g-C3N4. As a carbon material, biochar has a large specific surface area and good photoelectric properties. Compounding biochar with g-C3N4 can improve the photocatalytic activity to a certain extent. The Chinese invention patent with publication number CN 107376972A uses withered magnolia petals as a carbon source to prepare a biochar-modified carbon nitride composite photocatalyst, which can well degrade dithiobenzothiazole in environmental wastewater; the Chinese invention patent with publication number CN 109304203 A uses soybean stalks as a carbon source to prepare a biochar-loaded graphite phase carbon nitride composite photocatalyst, which can well degrade petroleum hydrocarbons in soil; however, although these g-C3N4 / biochar composite materials in the prior art have made certain research progress, there are still problems such as complex synthesis steps, long preparation cycle, high cost, and catalytic performance needs to be further improved, which cannot meet the performance requirements well. Summary of the invention

[0005] The object of the present invention is to provide a method and application of preparing g-C3N4 / biochar with high photocatalytic activity by molten salt pyrolysis of sewage sludge, so as to solve the above-mentioned problems in the background technology. The present invention uses sewage sludge as a carbon source to compound biochar with g-C3N4, which can increase the specific surface area of ​​the material, promote electron transfer, and thus improve the photocatalytic activity. The photocatalytic material prepared by the present invention has a narrow band gap width, a large visible light absorption range, and excellent photocatalytic activity. At the same time, using sewage sludge as a carbon source realizes the rational utilization of waste.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a method for preparing g-C3N4 / biochar by pyrolyzing sewage sludge with molten salt, comprising the following steps:

[0008] Drying the sewage sludge to obtain sludge powder;

[0009] The sludge powder and melamine are mixed to obtain a mixed material precursor, which is then mixed with a molten salt medium and subjected to pyrolysis treatment to obtain the g-C3N4 / biochar.

[0010] Preferably, the drying is to dry the sewage sludge at 80° C. to a constant weight and then pass it through a 200-mesh sieve.

[0011] Preferably, after the pyrolysis treatment, the steps of washing and drying are further included; the drying is performed at 80° C. for 24 hours.

[0012] Preferably, the iron element in the sludge powder accounts for 1-5%, and the aluminum element accounts for 10-15%.

[0013] Preferably, the mass ratio of the sludge powder to melamine is 1-10:1.

[0014] Preferably, the mass ratio of the molten salt medium to the mixed material precursor is 0.5-5:1.

[0015] Preferably, the melting point or eutectic point of the molten salt medium is ≤810° C.; the molten salt medium includes one or more of carbonates, chloride salts, nitrates and sulfates.

[0016] When the molten salt medium is a single-component salt, its melting point should not exceed 810° C.; when the molten salt medium is a mixture of multiple salts, the eutectic point of the mixed salt should not exceed 810° C. Further preferably, the molten salt medium is a chemically stable salt that does not decompose within the range of 400-800° C.

[0017] Preferably, the carbonate includes one or more of Li2CO3, Na2CO3, K2CO3 and CaCO3; the chloride salt includes one or more of LiCl, NaCl, KCl, CaCl2 and MgCl2; the nitrate includes one or more of LiNO3, NaNO3, KNO3 and Ca(NO3)2; the sulfate includes two or more of Li2SO4, Na2SO4, K2SO4 and CaSO4.

[0018] Preferably, the pyrolysis treatment is carried out under a protective atmosphere, heating the temperature to 400-800° C. at a heating rate of 10° C. / min and then keeping the temperature for 2 hours.

[0019] Preferably, the protective atmosphere is a nitrogen atmosphere.

[0020] The second technical solution of the present invention is to provide a g-C3N4 / biochar prepared according to the above method.

[0021] The third technical solution of the present invention is to provide an application of the above-mentioned g-C3N4 / biochar in the field of photocatalytic degradation of organic dyes.

[0022] Preferably, the organic dye is rhodamine B (RhB).

[0023] The fourth technical solution of the present invention is to provide an application of the above-mentioned g-C3N4 / biochar in the field of photocatalytic decomposition and hydrogen production.

[0024] The beneficial technical effects of the present invention are as follows:

[0025] (1) The preparation process of the present invention is simple, low-cost and has an ideal yield.

[0026] (2) The present invention uses sewage sludge as a carbon source to compound biochar with g-C3N4, which can increase the specific surface area of ​​the material, promote electron transfer, and thus improve photocatalytic activity.

[0027] (3) Due to the addition of flocculants in sewage treatment plants, sewage sludge is rich in iron. At the same time, sewage sludge contains solid particles such as mud and sand mixed in domestic sewage or industrial wastewater, which makes sewage sludge rich in aluminum. The doping of iron and aluminum elements is expected to expand the light response range of g-C3N4 and thus improve its photocatalytic performance.

[0028] (4) The molten salt in the present invention can provide a unique liquid-phase catalytic reaction environment. The use of molten salt pyrolysis is beneficial to the pore development of biochar, prompting it to form a large number of interconnected pores, thereby providing more active sites for photocatalytic reactions.

[0029] (5) Li in molten salt + 、Na + , K+ , Ca 2+ Doping with metal ions can further regulate the band gap width of g-C3N4 / biochar, which is more conducive to the improvement of photocatalytic activity, thereby improving the hydrogen production efficiency and the degradation rate of pollutants.

[0030] (6) The photocatalytic material prepared by the present invention has a narrow band gap width and a large visible light absorption range, and has excellent photocatalytic activity. At the same time, sewage sludge is used as a carbon source, thereby achieving reasonable utilization of waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 The XRD diagrams of the products of Comparative Examples 1-3 and Example 3 are shown in Figure 1. (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Comparative Example 3, and (d) is Example 3.

[0033] Figure 2 It is the UV-visible diffuse reflectance spectra of the products of Comparative Examples 1-3 and Example 3.

[0034] Figure 3 This is a photocatalytic hydrogen production performance diagram of the products of Comparative Examples 1-3 and Example 3.

[0035] Figure 4 The photocatalytic degradation performance diagram of RhB of the products of Comparative Examples 1-3 and Example 3 is shown. DETAILED DESCRIPTION

[0036] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0037] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0038] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0040] The sewage sludge used in the following embodiments and comparative examples of the present invention comes from the residual sludge of the Huangxiaohe Sewage Treatment Plant; the iron element in the sludge powder accounts for 4.2%, and the aluminum element accounts for 11.5%.

[0041] The "room temperature" in the present invention is 10-30°C unless otherwise specified.

[0042] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0043] Example 1

[0044] A method for preparing g-C3N4 / biochar by molten salt pyrolysis of sewage sludge, the steps are as follows:

[0045] (1) Preparation of mixed material precursor:

[0046] The sewage sludge is dried at 80° C. to a constant weight, and then sieved through a 200-mesh sieve to obtain sludge powder; the sludge powder is uniformly mixed with melamine at a mass ratio of 10:1 to obtain a mixed material precursor;

[0047] (2) Preparation of g-C3N4 biochar photocatalytic materials:

[0048] Li2CO3, Na2CO3 and K2CO3 were mixed in a molar ratio of 50.5:27.5:22 to prepare a molten salt medium; the molten salt medium and the mixed material precursor were weighed in a mass ratio of 0.5:1, the molten salt medium and the mixed material precursor were added to a crucible and wrapped with aluminum foil, the crucible was placed in a tubular furnace, and the temperature was increased to 700°C at 10°C / min under a nitrogen atmosphere, and kept at 700°C for 2h, then naturally cooled, washed with water, and dried at 80°C for 24h to obtain g-C3N4 / biochar.

[0049] Example 2

[0050] A method for preparing g-C3N4 / biochar by molten salt pyrolysis of sewage sludge, the steps are as follows:

[0051] (1) Preparation of mixed material precursor:

[0052] The sewage sludge is dried at 80° C. to a constant weight, and then sieved through a 200-mesh sieve to obtain sludge powder; the sludge powder is uniformly mixed with melamine at a mass ratio of 10:1 to obtain a mixed material precursor;

[0053] (2) Preparation of g-C3N4 biochar photocatalytic materials:

[0054] Li2CO3, Na2CO3 and K2CO3 were mixed in a molar ratio of 50.5:27.5:22 to prepare a molten salt medium; the molten salt medium and the mixed material precursor were weighed in a mass ratio of 0.5:1, the molten salt medium and the mixed material precursor were added into a crucible and wrapped with aluminum foil, the crucible was placed in a tubular furnace, and the temperature was increased to 400°C at 10°C / min under a nitrogen atmosphere, and kept at 400°C for 2h, then naturally cooled, washed with water, and dried at 80°C for 24h to obtain g-C3N4 / biochar.

[0055] Example 3

[0056] A method for preparing g-C3N4 / biochar by molten salt pyrolysis of sewage sludge, the steps are as follows:

[0057] (1) Preparation of mixed material precursor:

[0058] The sewage sludge is dried at 80° C. to a constant weight, and then sieved through a 200-mesh sieve to obtain sludge powder; the sludge powder is uniformly mixed with melamine at a mass ratio of 10:1 to obtain a mixed material precursor;

[0059] (2) Preparation of g-C3N4 biochar photocatalytic materials:

[0060] Li2CO3, Na2CO3 and K2CO3 were mixed in a molar ratio of 50.5:27.5:22 to prepare a molten salt medium; the molten salt medium and the mixed material precursor were weighed in a mass ratio of 5:1, the molten salt medium and the mixed material precursor were added into a crucible and wrapped with aluminum foil, the crucible was placed in a tubular furnace, and the temperature was increased to 700°C at 10°C / min under a nitrogen atmosphere, and kept at 700°C for 2h, then naturally cooled, washed with water, and dried at 80°C for 24h to obtain g-C3N4 / biochar.

[0061] Example 4

[0062] A method for preparing g-C3N4 / biochar by molten salt pyrolysis of sewage sludge, the steps are as follows:

[0063] (1) Preparation of mixed material precursor:

[0064] The sewage sludge is dried at 80° C. to a constant weight, and then sieved through a 200-mesh sieve to obtain sludge powder; the sludge powder is uniformly mixed with melamine at a mass ratio of 10:1 to obtain a mixed material precursor;

[0065] (2) Preparation of g-C3N4 biochar photocatalytic materials:

[0066] LiCl, NaCl and CaCl2 were mixed in a molar ratio of 47.5:15:37.5 to prepare a molten salt medium; the molten salt medium and the mixed material precursor were weighed in a mass ratio of 5:1, the molten salt medium and the mixed material precursor were added to a crucible, and wrapped with aluminum foil, and the crucible was placed in a tubular furnace, and the temperature was increased to 700°C at 10°C / min under a nitrogen atmosphere, and kept at 700°C for 2h, followed by natural cooling, washing with water, and then drying at 80°C for 24h to obtain g-C3N4 / biochar.

[0067] Example 5

[0068] A method for preparing g-C3N4 / biochar by molten salt pyrolysis of sewage sludge, the steps are as follows:

[0069] (1) Preparation of mixed material precursor:

[0070] The sewage sludge is dried at 80° C. to a constant weight, and then sieved through a 200-mesh sieve to obtain sludge powder; the sludge powder is uniformly mixed with melamine at a mass ratio of 1:1 to obtain a mixed material precursor;

[0071] (2) Preparation of g-C3N4 biochar photocatalytic materials:

[0072] Li2CO3, Na2CO3 and K2CO3 were mixed in a molar ratio of 50.5:27.5:22 to prepare a molten salt medium; the molten salt medium and the mixed material precursor were weighed in a mass ratio of 5:1, the molten salt medium and the mixed material precursor were added into a crucible and wrapped with aluminum foil, the crucible was placed in a tubular furnace, and the temperature was increased to 700°C at 10°C / min under a nitrogen atmosphere, and kept at 700°C for 2h, then naturally cooled, washed with water, and dried at 80°C for 24h to obtain g-C3N4 / biochar.

[0073] Comparative Example 1

[0074] A method for preparing a g-C3N4 photocatalytic material, the steps are as follows:

[0075] Weigh 5 g of melamine and add it to a 30 mL crucible. Cover the crucible with a lid and wrap it with aluminum foil. Place the crucible in a muffle furnace and heat it from room temperature to 700 °C at a heating rate of 10 °C / min. Keep it at 700 °C for 2 h. After cooling to room temperature with the furnace, pure g-C3N4 photocatalytic material can be obtained.

[0076] Comparative Example 2 (Omitting Molten Salt Medium)

[0077] A method for preparing a g-C3N4 / biochar photocatalytic material, comprising the following steps:

[0078] (1) Preparation of mixed material precursor:

[0079] The sewage sludge is dried at 80° C. to a constant weight, and then sieved through a 200-mesh sieve to obtain sludge powder; the sludge powder is uniformly mixed with melamine at a mass ratio of 10:1 to obtain a mixed material precursor;

[0080] (2) Preparation of g-C3N4 / biochar photocatalytic materials:

[0081] The mixed material precursor was added into a crucible and wrapped with aluminum foil. The crucible was placed in a tube furnace and heated to 700°C at 10°C / min under a nitrogen atmosphere. The crucible was kept at 700°C for 2 h, then cooled naturally, washed with water, and dried at 80°C for 24 h to obtain the g-C3N4 / biochar photocatalytic material.

[0082] Comparative Example 3 (Sewage sludge replaced with peanut shells)

[0083] A method for preparing g-C3N4 / biochar photocatalytic material by molten salt pyrolysis of peanut shells, the steps are as follows:

[0084] (1) Preparation of mixed material precursor:

[0085] The purchased peanut shells were washed with water and dried at 80°C to constant weight, crushed and sieved through a 200-mesh sieve to obtain peanut shell powder, and the peanut shell powder was uniformly mixed with melamine at a mass ratio of 10:1 to obtain a mixed material precursor;

[0086] (2) Preparation of g-C3N4 / biochar photocatalytic materials:

[0087] Li2CO3, Na2CO3 and K2CO3 were mixed in a molar ratio of 50.5:27.5:22 to prepare a molten salt medium; the molten salt medium and the mixed material precursor were weighed in a mass ratio of 5:1, the molten salt medium and the mixed material precursor were added into a crucible and wrapped with aluminum foil, the crucible was placed in a tubular furnace, and the temperature was increased to 700°C at 10°C / min under a nitrogen atmosphere, and kept at 700°C for 2h, then naturally cooled, washed with water, and dried at 80°C for 24h to obtain g-C3N4 / biochar.

[0088] Effect verification

[0089] 1. Figure 1The XRD diagrams of the products of Comparative Examples 1-3 and Example 3 are shown in Figure 1. (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Comparative Example 3, and (d) is Example 3.

[0090] Depend on Figure 1 It can be seen that in the samples of g-C3N4 / biochar prepared under nitrogen atmosphere (Comparative Example 2), g-C3N4 / biochar prepared by molten salt pyrolysis of peanut shells (Comparative Example 3), and g-C3N4 / biochar prepared by molten salt pyrolysis of sewage sludge (Example 3), the peak at 22.2° may be the characteristic peak of amorphous carbon, indicating that the biochar has been compounded into g-C3N4; all samples have a strong peak at 27.5°, which is consistent with the diffraction angle of pure graphite phase carbon nitride, indicating that the prepared photocatalyst is consistent with the crystal form of pure graphite phase carbon nitride, proving that the biochar modification process of the present invention does not damage its basic structure.

[0091] 2. Figure 2 It is the UV-visible diffuse reflectance spectra of the products of Comparative Examples 1-3 and Example 3.

[0092] Depend on Figure 2 It can be seen that the absorption boundary of pure g-C3N4 (Comparative Example 1) can be calculated by the intercept method to be 474nm, and the corresponding band gap is 2.62eV; the absorption boundary of g-C3N4 / biochar (Comparative Example 2) prepared in a nitrogen atmosphere is extended to the visible light region of about 498nm, and the corresponding band gap is 2.49eV, indicating that the response range of the catalyst to visible light is enhanced after biochar modification, but it is still relatively small; the absorption boundary of g-C3N4 / biochar (Comparative Example 3) prepared by molten salt pyrolysis of peanut shells is extended to the visible light region of about 510nm, and the corresponding band gap is 2.43eV, while the absorption boundary of g-C3N4 / biochar (Example 3) prepared by molten salt pyrolysis of sewage sludge is further extended to about 523nm, and the corresponding band gap is 2.37eV, indicating that the use of molten salt pyrolysis to prepare g-C3N4 / biochar can further regulate the band gap of the composite material and expand its light response range.

[0093] 3. Evaluate the performance of photocatalytic hydrogen production. The specific test method is: use Pt as a co-catalyst, triethanolamine as a sacrificial agent, and use a photocatalytic water splitting hydrogen production system for testing; add 50 mg of the prepared photocatalyst to a solution of 90.0 mL of deionized water and 10 mL of triethanolamine, and add H2PtCl6·6H2O (the addition amount is 3%, based on the mass of Pt). Evacuate the system before testing, and connect cooling water during the entire test process to keep the reaction system at room temperature. Turn on the light source (300W xenon lamp, filter λ>420nm), carry out a photocatalytic reaction, and use online gas chromatography analysis technology to determine the hydrogen produced by the reaction. The test results are as follows Figure 3 shown.

[0094] Figure 3 This is a photocatalytic hydrogen production performance diagram of the products of Comparative Examples 1-3 and Example 3.

[0095] Depend on Figure 3 It can be seen that under visible light, the rate of hydrogen production from water by the g-C3N4 / biochar photocatalytic material prepared by the molten salt pyrolysis method reached 416 μmol / h / g, which is higher than the hydrogen production rate of Comparative Example 1, Comparative Example 2, and Comparative Example 3, indicating that the g-C3N4 / biochar photocatalytic material prepared by the molten salt pyrolysis method of the present invention has higher visible light water decomposition hydrogen production activity.

[0096] 4. Evaluate the performance of photocatalytic degradation of RhB. The specific test method is: add 50 mg of the prepared photocatalyst to 50 mL of prepared RhB solution (RhB concentration is 10 mg / L), react in the dark for 30 minutes, so that the photocatalyst completes the adsorption-desorption equilibrium of RhB in the solution, and then place the solution under a light source (300W xenon lamp, filter λ>420nm), stir magnetically, and perform photocatalytic reaction; use a UV-visible spectrophotometer to measure the absorbance of the test solution at 552nm (the wavelength of the maximum characteristic peak of the RhB solution) to detect the concentration change of the RhB solution. The test results are as follows: Figure 4 shown.

[0097] Figure 4 The photocatalytic degradation performance diagram of RhB of the products of Comparative Examples 1-3 and Example 3 is shown.

[0098] Depend on Figure 4 It can be seen that under visible light, the g-C3N4 / biochar photocatalytic material prepared by molten salt pyrolysis can completely degrade the RhB solution within 80 minutes, and the degradation efficiency is higher than that of pure g-C3N4 (Comparative Example 1), g-C3N4 / biochar prepared in nitrogen atmosphere (Comparative Example 2) and g-C3N4 / biochar prepared by molten salt pyrolysis of peanut shells (Comparative Example 3).

[0099] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing g-C3N4 / biochar by molten salt pyrolysis of sewage sludge, characterized in that: The following steps are involved: Drying the sewage sludge to obtain sludge powder; The sludge powder and melamine are mixed to obtain a mixed material precursor, which is then mixed with a molten salt medium and subjected to pyrolysis treatment to obtain the g-C3N4 / biochar.

2. The method according to claim 1, characterized in that The iron element in the sludge powder accounts for 1-5%, and the aluminum element accounts for 10-15%.

3. The method according to claim 1, characterized in that: The mass ratio of the sludge powder to melamine is 1-10:

1.

4. The method according to claim 1, characterized in that: The mass ratio of the molten salt medium to the mixed material precursor is 0.5-5:

1.

5. The method according to claim 1, characterized in that The melting point or eutectic point of the molten salt medium is ≤810°C; the molten salt medium includes one or more of carbonates, chlorides, nitrates and sulfates.

6. The method according to claim 5, characterized in that The carbonate includes one or more of Li2CO3, Na2CO3, K2CO3 and CaCO3; the chloride salt includes one or more of LiCl, NaCl, KCl, CaCl2 and MgCl2; the nitrate includes one or more of LiNO3, NaNO3, KNO3 and Ca(NO3)2; the sulfate includes two or more of Li2SO4, Na2SO4, K2SO4 and CaSO4.

7. The method according to claim 1, characterized in that The pyrolysis treatment is carried out under a protective atmosphere, heating the temperature to 400-800° C. at a heating rate of 10° C. / min, and then keeping the temperature for 2 hours.

8. A g-C3N4 / biochar prepared according to the method according to any one of claims 1 to 7.

9. Use of the g-C3N4 / biochar as claimed in claim 8 in the field of photocatalytic degradation of organic dyes.

10. An application of the g-C3N4 / biochar as claimed in claim 8 in the field of photocatalytic decomposition and hydrogen production.

Citation Information

Patent Citations

  • Mesoporous C3N4 photocatalytic material prepared by using molten salt method and application thereof in photocatalysis field

    CN102992282A

  • Preparation method for carbon nitride visible-light-induced photocatalyst

    CN105772055A

  • Carbon nitride photocatalytic material and preparation method thereof

    CN110280289A

  • Two-dimensional porous nitrogen-doped carbon, preparation method thereof, and application of two-dimensional porous nitrogen-doped carbon in lithium ion battery

    CN111362249A

  • Green method for preparing multifunctional biochar from sludge and application of biochar

    CN115259131A

Cited By

  • Anaerobic sludge-g-C3N4 composite material as well as preparation method and application thereof

    CN121623830A

  • An anaerobic sludge-g-C3N4 composite material, its preparation method and application

    CN121623830B